Bringing treasures and placing fears: Old Kingdom epithets and titles related to activities abroad - Diego Espinel, Andrés (ISIMU, 2017)
The present study analyses two epithets related to the Egyptian activities abroad: “who brings the produce from the foreign countries” (inn(.w) xr(y.w)t m xAs.wt) and its variants, and “who places the fear of Horus in the foreign countries” (dd(.w) nrw Hrw m xAs.wt). As with other Old Kingdom epithets, they have generally been overlooked as informative data on the administrative roles and vital experiences of their holders. In order to evaluate their potential significance as sources of information, both expressions are brought into connection with the titles of their holders and related biographical accounts. As a result, the epithets become complementary data that help to profile the actual functions and actions of these officials. For the sake of completion, certain titles related to the acquisition of intelligence are also included in this study. Moreover, further thoughts on the possible origins and values of Old Kingdom epithets are also presented.